cDNA Cloning and Partial Characterization of the DJ-1 Gene from Tribolium castaneum - Shunya Sasaki; Maaya Nishiko; Takuma Sakamoto; Michael R. Kanost; Hiroko Tabunoki (MDPI AG, 2021)
The DJ-1 gene is highly conserved across a wide variety of organisms and it plays a role in anti-oxidative stress mechanisms in cells. The red flour beetle, Tribolium castaneum, is widely used as a model insect species because it is easy to evaluate gene function in this species using RNA interference (RNAi). The T. castaneum DJ-1 (TcDJ-1) sequence is annotated in the T. castaneum genome database; however, the function and characteristics of the TcDJ-1 gene have not been elucidated. Here, we investigated the cDNA sequence of TcDJ-1 and partially characterized its function. First, we examined the TcDJ-1 amino acid sequence and found that it was highly conserved with sequences from other species. TcDJ-1 mRNA expression was higher in the early pupal and adult developmental stages. We evaluated oxidant tolerance in TcDJ-1 knockdown adults using paraquat and found that adults with TcDJ-1 knockdown exhibited increased sensitivity to paraquat. Our findings show that TcDJ-1 has an antioxidant function, as observed for DJ-1 from other insects. Therefore, these results suggest that TcDJ-1 protects against oxidative stress during metamorphosis.